Diversity Assessment of Foxtail Millet (Setaria Italica L. Beauv) Accessions Collected from Different Locations of Nepal - Sapkota, Manoj; Pandey, Madhav Prasad; Thapa, Dhruba Bahadur; Yadav, Mukesh Kumar; Ghimire, Sapana; Timalsina, Dipak (International Journal of Applied Sciences and Biotechnology, 2017)
Foxtail millet (Setaria italica L. Beauv) categorized as an underutilized crop in Nepal persist a large diversity among different germplasms and accessions found in the country. Ten foxtail millet accessions were collected from different parts of Nepal and were evaluated for assessing the diversity in different characters at Institute of Agriculture and Animal Science, Rampur, Chitwan. The accessions were experimented in Randomized Complete Block Design with three replications. Observations were taken for qualitative traits i.e. tip of first leaf, anthocyanin at leaf base, lobe compactness, length of bristles, anthocyanin presence, leaf blade altitude, flag leaf color, lobe in panicles, panicle lodging, inflorescence compactness, overall color, panicle anthocyanin, panicle shape and growth habit. Shannon Weiner index and Evenness were calculated to assess the diversity in the accessions under study. The maximum number of diversity in traits of lobe compactness of panicle (1.3624) followed by panicle lodging (1.1595), inflorescence compactness (1.1235) and length of bristles (1.0681). Least diversity was observed in trait of growth habit (0.3926) followed by panicle anthocyanin coloration (0.4505) and lobes in panicles (0.5799). The finding of existence of wide diversity in the studied accessions could be a pivotal information for further study of genetic variation of foxtail millet germplasms.Int J Appl Sci Biotechnol, Vol 4(4): 483-488